Respuesta :

Answer:

x = 3, (3, -34)

Step-by-step explanation:

Please write this as y = -x^2 - 6x - 7.  Here we use " ^ " to indicate exponentiation.  The coefficients of this quadratic equation are a = -1, b = -6 and c = -7.

                                                                                -b

Using the formula for the axis of symmetry, x = --------

                                                                                 2a

                                                                  -(-6)

we find that this axis in this case is x = ---------- = 6/2 = 3.

                                                                  2(-1)

The axis of symmetry is x = 3.

We use this x value to determine the y-value at the vertex:

y = -(3)^2 - 6(3) - 7 = -9 - 18 - 7 = -34

The vertex is (3, -34).